Maxillary advancement versus mandibular setback in class III dentofacial deformity: are there any differences in aesthetic outcomes?. Issue 4 (April 2017) - Ghassemi, M.; Hilgers, R.-D.; Fritz, U.; Modabber, A.; Ghassemi, A.
Abstract: A retrospective evaluation of maxillary advancement and mandibular setback in class III patients was performed and their aesthetic outcomes compared. Patients with a sella–nasion–A-point angle (SNA) of 80–84° were selected. Pre- and postoperative lateral cephalograms were obtained for 34 class III patients; these were divided into two groups according to the surgical procedure performed: mandibular setback group ( n  = 17) and maxillary advancement group ( n  = 17). The pre- and postoperative cervical length, lip–chin–throat angle, lower/upper lip thickness, distance from the lower/upper lip to the aesthetic line, soft tissue angle, facial contour angle, and nasolabial angle of the two groups were compared. Significant differences were observed for cervical length ( P  = 0.0003) and sex ( P  = 0.003) when comparing maxillary advancement with mandibular setback. Although the preoperative cervical length was similar in the two groups, it increased significantly after maxillary advancement and decreased after mandibular setback. In this study, the differences in aesthetic outcomes depending on the surgical procedure performed were considered. Some aesthetically important parameters proved to be superior after maxillary advancement when compared to mandibular setback, even with the maxilla in the normal position.